High Temperature Cyclic Oxidation of Yttrium Modified Aluminide Diffusion Coatings of Stainless Steel - Mohammed Hussein, Rajab (Anbar Journal of Engineering Sciences, 2009)
In this study, yttrium and aluminum were simultaneously co-deposited by diffusion into austenitic stainless steel (AISI 316L) substrates, by a single-step pack cementation process. Cyclic oxidation tests were conducted on the aluminide coating and on the yttrium modified aluminide coating of stainless steel in air under atmospheric pressure at temperatures 700 C° and 800 C° for 100h at 10h cyclic. Optical metallography and X-ray diffraction (XRD) techniques were used to characterize the changes in scale morphology and to identify the phases and oxidation products. The yttrium modified aluminde coating showed very good cyclic oxidation resistance compared to aluminide coating